Adsorption of anti-inflammatory nimesulide by graphene materials: a combined theoretical and experimental study. Issue 33 (10th August 2017) - Jauris, I. M.; Matos, C. F.; Zarbin, A. J. G.; Umpierres, C. S.; Saucier, C.; Lima, E. C.; Fagan, S. B.; Zanella, I.; Machado, F. M.
Abstract : Interactions of anti-inflammatory nimesulide with different graphene material species were explored employing both ab initio calculations and a batch adsorption process. Abstract : Interactions of anti-inflammatory nimesulide (NM) with different graphene material species were explored employing both ab initio calculations, based on Density Functional Theory (DFT), and a batch adsorption process. The adsorption of NM onto graphene, with and without a vacancy, reduced graphene oxide (rGO) and functionalized graphene nanoribbons was simulated, providing a good understanding of the adsorption process of the NM molecule onto graphene material surfaces. The theoretical results indicate a physisorption interaction between NM and all of the evaluated adsorbents. Based on batch adsorption experiments, it was found that rGO, obtained via a modified Hummers method, is a good nanoadsorbent for the removal of the anti-inflammatory NM from aqueous solutions. The general-order kinetic equation displays the best fit to the experimental data compared with pseudo-first order and pseudo-second order kinetics. The equilibrium data fitted well into the Liu isotherm equation, and the maximum sorption capacity for the adsorption of NM by rGO was 82.4 mg g −1 at 25 °C. Our results of the first principle calculations and the batch adsorption experiments point out that graphene materials are promising nanomaterials for extracting NM from aqueous solutions.